Weak genetic divergence and signals of adaptation obscured by high gene flow in an economically important aquaculture species - Bernarda Calla; Jingwei Song; Neil Thompson (BMC Genomics)
Abstract Background The genetic diversity of a population defines its ability to adapt to episodic and fluctuating environmental changes. For species of agricultural value, available genetic diversity also determines their breeding potential and remains fundamental to the development of practices that maintain health and productivity. In this study, we used whole-genome resequencing to investigate genetic diversity within and between naturalized and captively reared populations of Pacific oysters from the US Pacific coast. The analyses included individuals from preserved samples dating to 1998 and 2004, two contemporary naturalized populations, and one domesticated population. Results Despite high overall heterozygosity, there was extremely low but significant genetic divergence between populations, indicative of high gene flow and/or little variability from founding events. The captive population, which was reared for over 25 years was the most genetically distinct population and exhibited reduced nucleotide diversity, attributable to inbreeding. Individuals from populations that were separated both geographically and temporally did not show detectable genetic differences, illustrating the consequences of human intervention in the form translocation of animals between farms, hatcheries and natural settings. Fifty-nine significant F ST outlier sites were identified, the majority of which were present in high proportions of the captive population individuals, and which are possibly associated with domestication. Conclusion Pacific oysters in the US Pacific coast harbor high genetic heterozygosity which obscures weak population structure. Differences between these Pacific oyster populations could be leveraged for breeding and might be a source of adaptation to new environments.